The basic helix–loop–helix transcription factors MYC1 and MYC2 have a dual role in the regulation of constitutive and stress‐inducible specialized metabolism in tomato. Issue 3 (15th August 2022) - Swinnen, Gwen; De Meyer, Margaux; Pollier, Jacob; Molina‐Hidalgo, Francisco Javier; Ceulemans, Evi; Venegas‐Molina, Jhon; De Milde, Liesbeth; Fernández‐Calvo, Patricia; Ron, Mily; Pauwels, Laurens; Goossens, Alain
Summary: Plants produce specialized metabolites to protect themselves from biotic enemies. Members of the Solanaceae family accumulate phenylpropanoid–polyamine conjugates (PPCs) in response to attackers while also maintaining a chemical barrier of steroidal glycoalkaloids (SGAs). Across the plant kingdom, biosynthesis of such defense compounds is promoted by jasmonate signaling in which clade IIIe basic helix–loop–helix (bHLH) transcription factors play a central role. By characterizing hairy root mutants obtained through Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR)‐CRISPR associated protein 9 (CRISPR‐Cas9) genome editing, we show that the tomato clade IIIe bHLH transcription factors, MYC1 and MYC2, redundantly control jasmonate‐inducible PPC and SGA production, and are also essential for constitutive SGA biosynthesis. Double myc1 myc2 loss‐of‐function tomato hairy roots displayed suppressed constitutive expression of SGA biosynthesis genes, and severely reduced levels of the main tomato SGAs α‐tomatine and dehydrotomatine. In contrast, basal expression of genes involved in PPC biosynthesis was not affected. CRISPR‐Cas9(VQR) genome editing of a specific cis ‐regulatory element, targeted by MYC1/2, in the promoter of a SGA precursor biosynthesis gene led to decreased constitutive expression of this gene, but did not affect its jasmonate inducibility. Our results demonstrate that clade IIIe bHLH transcriptional regulators have evolved under the control of distinct regulatory cues to specifically steer constitutive and stress‐inducible specialized metabolism.